Determinants of tax non-compliance behaviour of business income earners in Shah Alam - Zahrul Zaid, Abdul Wahab (2017)
Tax authorities around the world continuously attempt to improve the level of tax compliance including Inland Revenue Board of Malaysia (IRBM) by combating tax non-compliance. IRBM defines tax non-compliance as the failure of an individual or an entity to register, submit tax forms within a prescribed time period, report the correct amount of income, and pay taxes. Previous studies confirmed that most individual category taxpayers are involved with tax non-compliance activities, however not many studies covered this issue in Malaysia especially on individuals who are business income earners. Thus, this study empirically investigates the influence of tax knowledge, tax morale and tax complexity on tax non-compliance behaviour of business income earners in Shah Alam. This study is supported by behavioural decision theory and theory of cognitive conflict. The data was collected through survey questionnaires and analysed using multiple regression analysis and other statistical techniques. A total of 500 questionnaires were distributed that yielded 328 usable questionnaires. The results reveal that there is a positive significant relationship between tax knowledge, tax morale and tax complexity on tax noncompliance behaviour of business income earners. This study concludes with the theoretical implications and practical recommendations for IRBM in order to improve tax collection such as developed and implement more stringent enforcement strategies to combat tax non-compliance in Malaysia. In addition, IRBM should play a more proactive role to encourage and educate business income earners by enhancing their knowledge on taxation. This study also highlights several limitations and suggests future studies in this area.